Pengaruh Pemasaran Digital Dan Online Customer Review Tehadap Keputusan Pembelian Pada Produk UMKM Lumpia Beef Zoeya Di Instagram - Anggi Syapira Purba; Dinda Nur Shaibah; Bobby Hartanto; Willy Cahyadi (CV. ITTC INDONESIA, 2026)
The use of Instagram as a marketing medium for MSMEs continues to grow, but its effectiveness in driving consumer purchasing decisions has not been widely studied in the context of local culinary MSMEs. This study aims to examine the influence of digital marketing and online customer reviews on purchasing decisions for the MSME product Lumpia Beef Zoeya, marketed through Instagram. This research used a quantitative method with a causal associative approach, aiming to determine the relationship between the independent and dependent variables. The study population included all consumers of Lumpia Beef Zoeya who made purchases between January and March 2026, either directly at the outlet in Tanah Lapang Sri Mersing or online through Instagram and GoFood. This study involved 104 respondents selected using a purposive sampling technique, which selects samples based on specific criteria that align with the research objectives. Primary data was collected through a questionnaire with a 5-point Likert scale. The data was then processed and analyzed using SmartPLS 3.0 software, using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results of the study indicate that digital marketing has a positive and significant effect on purchasing decisions, with a path coefficient of 0.345 and a t-statistic of 2.115. Online customer reviews also have a positive and significant effect on purchasing decisions, with a path coefficient of 0.561 and a t-statistic of 3.602, and are the most dominant variables. Together, these two variables explain 76.6% of the variation in consumer purchasing decisions. These findings imply that MSMEs need to optimize their digital content strategies to attract and encourage consumers to actively provide positive reviews to improve purchasing decisions.